Photo sharing platform targeted at users with social anxiety - Lim, Isaac Yong Xuan (Nanyang Technological University, 2021)
Over the years, social media has grown to be an integral part of our lives. Though social media platforms allow users to share information and stay connected with one another, and were created with a good intention in mind, it has also affected the mental health of some: the issue of social anxiety. Comparisons with peers and overthinking of comments or responses one receives on social media, leads to lower self-esteem are some of the common issues that people face while having social media anxiety [1]. This project aims to create a photo sharing platform that seeks to eliminate some of the worries that people experiencing social media anxiety might face. The goal is to implement features such as a profanity filter and an anonymity feature that protects the user and at the same time not taking away too much from what is expected from a photo sharing platform. The project has also been developed while keeping scalability in mind.